Jogja Fashion Week Carnival Costume in The Context of Locality - Setiawan, Deni (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2015)
Jogja Fashion Week Carnival (JFWC) is held in order to promote the development of costume creative industry in Indonesia, especially in Yogyakarta. Woven and batik (Javanese traditional fabric) as products of Indonesia is reproduced into art costumes. It may add the value of both the product and the price of the product itself as the core of the continuity of the creative industry economy in Indonesia. The eastern value of the costume design worn during the carnival may reflect the traditional value of society. The concept of the costume making is rooted from Indonesia folklores, legends and myths that are still being developed in present society. Throughout the event, exploration done by the artists is seen as a genuine attempt to support the Government in promoting costume industry both in national and international scale. Costumes worn in JFWC were analysed using aesthetic theory by adopting the point of view of DeWitt Henry Parker. The point of view comprises three main aesthetic principles, i.e.: an intact unity, thematic principle, as well as balance principle. Those three concepts can be used to find out the basic locality value of a costume that later can be used as the art educationâ€™s source of material. Finally, it is concluded that the theme of JFWC costume creation concept is sourced from the rich tradition of Indonesian society.Â